UTILIZATION OF INSTRUCTIONAL MATERIALS FOR TEACHING AND LEARNING OF BUSINESS STUDIES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study determined the utilization of instructional materials in teaching andlearning of business studies in secondary schools in Anambra State. Two researchquestions guided the study and two null hypotheses were. Descriptive surveyresearch design was adopted for the study. The population of the study comprised296 business subject teachers in all public secondary schools in Anambra State. Afive point rating scale questionnaire which was validated by experts was used fordata collection. Cronbach alpha was used to test the reliability of the instrument andreliability index of .82 was obtained. Data collected from the study were analyzedusing mean and standard deviation to answer the research questions and ascertainthe homogeneity of the respondents while Analysis of Variance (ANOVA) was usedto test the hypotheses at 0.05 level of significance. The results showed that thebusiness studies teachers seldomly utilized projected visual instructional materialsand often utilized non-projected visual instructional materials in teaching. Thefindings further revealed that teachers did not differ significantly in their meanratings based on years of experience.It was concluded that utilization ofinstructional materials by business studies teachers should help secondary schoolstudents acquire entrepreneurial skills that will enable them to be self-sufficient inthe competitive world of work. Based on the findings, the researchers recommended,among others, that relevant authorities should organize seminars, in-servicetraining, conferences and workshops for business studies teachers on the utilizationof instructional materials for effective learning outcomes.